Tracking official development assistance for reproductive health in conflict‐affected countries: 2002—2011. (28th January 2016) - Patel, P; Dahab, M; Tanabe, M; Murphy, A; Ettema, L; Guy, S; Roberts, B
Abstract : Objective: To provide information on trends on official development assistance (ODA) disbursement patterns for reproductive health activities in 18 conflict‐affected countries. Design: Secondary data analysis. Sample: 18 conflict‐affected countries and 36 non‐conflict‐affected countries. Methods: The Creditor Reporting System (CRS) database was analyzed for ODA disbursement for direct and indirect reproductive health activities to 18 conflict‐affected countries (2002–2011). A comparative analysis was also made with 36 non‐conflict‐affected counties in the same 'least‐developed' income category. Multivariate regression analyses examined associations between conflict status and reproductive health ODA and between reproductive needs and ODA disbursements. Main outcome measures: Patterns of ODA disbursements (constant U.S. dollars) for reproductive health activities. Results: The average annual ODA disbursed for reproductive health to 18 conflict‐affected countries from 2002 to 2011 was US$ 1.93 per person per year. There was an increase of 298% in ODA for reproductive health activities to the conflict‐affected countries between 2002 and 2011; 56% of this increase was due to increases in HIV/AIDS funding. The average annual per capita reproductive health ODA disbursed to least‐developed non‐conflict‐affected countries was 57% higher than to least‐developed conflict‐affected countries. Regression analyses confirmed disparities in ODA to and between conflict‐affected countries. Conclusions: Despite increases in ODA for reproductive health for conflict‐affected countries (albeit largely for HIV/AIDS activities), considerable disparities remains. Tweetable abstract: Study tracking 10 years of aid for reproductive aid shows major disparities for conflict‐affected countries. Tweetable abstract: Study tracking 10 years of aid for reproductive aid shows major disparities for conflict‐affected countries.